Speed and power predictors of change of direction ability in elite snow athletes - Schultz, F. A.; Cavazzoni, P.; Carnevale, R. V.; Abad, C. C. C.; Kobal, R.; Pereira, L. A.; Loturco, I. (Journal of Human Sport & Exercise, 2015)
Change of direction ability (COD speed) is an important physical component of snow sports. The aim of this study was to investigate the relationships between regular speed and vertical jumping ability, and COD speed in elite snow athletes. Moreover, the correlations between relative mean propulsive power (assessed in the jump squat exercise) and COD speed were quantified. Sixteen elite snow sport athletes executed squat jumps, countermovement jumps, jump squats, and 25 m sprint tests, in addition to a Zig-zag change of direction speed test. The outcomes revealed that vertical jumping height and mean propulsive power are strongly correlated (r ˜ 0.90) with COD speed. Furthermore, snow athletes capable of sprinting faster in a linear course of 25 m performed better in COD speed tests ( r = 0.91). Our results support the use of loaded and unloaded vertical jumping and regular speed tests to evaluate/monitor predictors of COD speed in elite snow athletes. Finally, these relationships suggest that plyometrics and regular speed training should be considered by coaches as effective strategies to enhance COD ability in this specific group of subjects.